Recurrent wheezing in preterm infants: Prevalence and risk factors - Maria Cristina Ribeiro dos Santos Simões; Yuri Inoue; Natasha Y. Matsunaga; Maria R.V. Carvalho; Gisleine L.T. Ribeiro; Eliane O. Morais; Maria A.G.O. Ribeiro; André M. Morcillo; José D. Ribeiro; Adyléia A.D.C. Toro (Elsevier, 2019)
Objective: To evaluate the prevalence and risk factors associated with progression to recurrent wheezing in preterm infants. Methods: The cross-sectional study was carried out in 2014 and 2015 and analyzed preterm infants born between 2011 and 2012. The search for these children was performed in a university maternity hospital and a Special Immunobiological Reference Center. The evaluation was performed through a questionnaire applied during a telephone interview. Results: The study included 445 children aged 39 (18-54) months. In the univariate analysis, the risk factors with the greatest chance of recurrent wheezing were birth weight <1000 g, gestational age <28 weeks, living with two or more siblings, food allergy, and atopic dermatitis in the child, as well as food allergy and asthma in the parents. In the multivariate analysis, there was a significant association between recurrent wheezing and gestational age at birth <28 weeks, food allergy and atopic dermatitis in the child, and living with two or more children. Of the 445 analyzed subjects, 194 received passive immunization against the respiratory syncytial virus, and 251 preterm infants were not immunized. There was a difference between the gestational age of these subgroups (p < 0.001). The overall prevalence of recurrent wheezing was 27.4% (95% CI: 23.42-31.70), whereas in the children who received passive immunization it was 36.1% (95% CI: 29.55-43.03). Conclusions: Personal history of atopy, lower gestational age, and living with two or more children had a significant association with recurrent wheezing. Children with lower gestational age who received passive immunization against the respiratory syncytial virus had a higher prevalence of recurrent wheezing than the group with higher gestational age. Resumo: Objetivo: Avaliar a prevalência e os fatores de risco associados à evolução para sibilância recorrente em prematuros. Métodos: O estudo transversal foi feito em 2014 e 2015 e analisou crianças prematuras nascidas entre 2011 e 2012. A busca dessas crianças foi feita em maternidade de hospital universitário e em um Centro de Referência para Imunobiológicos Especiais. A avaliação foi feita por questionário dirigido em entrevista telefônica. Resultados: O estudo incluiu 445 crianças com 39 (18-54) meses de vida. Na análise univariada, os fatores de risco com maior chance de sibilância recorrente foram peso de nascimento menor do que 1.000 g, idade gestacional menor do que 28 semanas, convivência com dois ou mais irmãos, alergia alimentar e dermatite atópica na criança e alergia alimentar e asma nos pais. Na análise multivariada houve associação significativa entre sibilância recorrente e idade gestacional ao nascer menor do que 28 semanas, alergia alimentar e dermatite atópica na criança e a convivência com duas ou mais crianças. Dos 445 sujeitos analisados, 194 receberam imunização passiva contra vírus sincicial respiratório e 251 eram prematuros não imunizados. Houve diferença entre a idade gestacional desses subgrupos (p < 0,001). A prevalência geral de sibilância recorrente foi 27,4% (IC 95%: 23,42-31,70) e nas crianças que receberam a imunização passiva foi 36,1% (IC 95%: 29,55-43,03). Conclusões: História pessoal de atopia, menor idade gestacional e convivência com duas ou mais crianças apresentaram associação significativa com sibilância recorrente. As crianças com menor idade gestacional, que receberam a imunização passiva contra o vírus sincicial respiratório, apresentaram maior prevalência de sibilância recorrente que o grupo de maior idade gestacional. Keywords: Asthma, Respiratory sounds, Respiratory syncytial virus, Prevalence, Risk factors, Prevention and control, Palavras-chave: Asma, Sons respiratórios, Vírus sincicial respiratório, Prevalência, Fatores de risco, Prevenção e controle